2021
DOI: 10.2147/amep.s272745
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Relationship of Perceived Learning Engagement, Motivation, and Academic Performance Among Nursing Students: A Multisite Study

Abstract: Background Learning engagement, motivation and academic achievement are vital growing areas in academic research. Evidence suggests that students’ engagement and motivation are positively linked to improved quality of learning. However, limited number of research studies have been conducted within this scope. Therefore, the present study was conducted to investigate the relationship of learning engagement, motivation and academic performance among university nursing students. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The benefit of disclosing and exchanging information that affects their motivation to learn they are include: information about their challenge, the support provided for them and how to access the support provided for them, goal orientation (Supervia et al, 2019), strategy to deal with challenge (F. Y. , learning strategy (Tsai2020), reassurance to about their efficacy (Sharififard et al, 2020). Then, motivation to learn influences academic performance, as confirmed by previous studies (Bayoumy & Alsayed, 2021;Sharififard et al, 2020). Elmer et al (2017) found correlation between emotional well-being and having more friends in their strong-tied network.…”
Section: Discussionsupporting
confidence: 53%
“…The benefit of disclosing and exchanging information that affects their motivation to learn they are include: information about their challenge, the support provided for them and how to access the support provided for them, goal orientation (Supervia et al, 2019), strategy to deal with challenge (F. Y. , learning strategy (Tsai2020), reassurance to about their efficacy (Sharififard et al, 2020). Then, motivation to learn influences academic performance, as confirmed by previous studies (Bayoumy & Alsayed, 2021;Sharififard et al, 2020). Elmer et al (2017) found correlation between emotional well-being and having more friends in their strong-tied network.…”
Section: Discussionsupporting
confidence: 53%
“…The results of statistical analysis showed a relationship between learning motivation and student learning activities with the original statistical value of the sample (O) 0.437, sample mean (M) 0.437, standard deviation (STDEV) 0.089, T statistic 4.900 and p values 0.000. Meanwhile, research conducted by previous study found that one of the factors that make students active in learning is the school curriculum (Bayoumy & Alsayed, 2021), it emphasizes that the subjects students study offer a diversity of learning opportunities that can increase student learning activities.…”
Section: The Relationship Between Learning Motivation and Student Lea...mentioning
confidence: 99%
“…Study assessing the role of self-regulated learning, learning motivation and task delays on the development of student learning competencies (Pelikan et al, 2021). Study researching learning engagement, motivation and academic performance of students (Bayoumy & Alsayed, 2021). Previous study that researching students' learning engagement during the COVID-19 Pandemic (Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, elements such as engagement, motivation, and academic achievement are vital aspects in academic research as such. Interestingly, evidence suggests that the student involvement and motivation are positively associated with the improved quality of learning (Mohamed Mohamed Bayoumy and Alsayed, 2021 ). Such students who are truly motivated can see learning as an opportunity to fulfill their own curiosity and eagerness for knowledge (Rose, 2011 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%